(untitled) (Journal of the College of Education for Women, 2018)
The aimed of the research was recognize the Big five personality factors and Academic procrastination among Baghdad university students, recognized differences between the gender according to Big five personality factors and Academic procrastination , to recognized differences between specialization (scientific, human), and to recognize the relationship Between the variables of the research, and the extend of contribution Big five personality factors in Academic procrastination , to achieve these aims , Adopt scale to measure the Big five personality factors for (John Danahue & Kentle) , As we as the preparation of scale Based on An amber of previous scales to measure Academic procrastination, After processing the data statistically using the (T-Test one sample, Pearson correlation coefficient, Multiple regression analysis) . The results of this research show that : the sample has enjoy four factors of the Big five personality (openness to experiences , Conscientiousness, Agreeableness, Neuroticism), Average level of Academic procrastination variable , there are statistically significant differences to extraversion and Conscientiousness variables and Male favor , and , Neuroticism variable and females favor , there are statistically significant differences according to specialization variable in the Agreeableness factor and human specialization favor , there are no statistically significant differences according to gender variable in Academic procrastination but there are differences according to specialization variable and scientific favor , the Conscientiousness factor has statistically significations contribution in Academic procrastination but the Neuroticism are positive contribution.